2020
DOI: 10.1186/s12943-020-01273-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment monitoring of colorectal cancer by integrated analysis of plasma concentration and sequencing of circulating tumor DNA

Abstract: Circulating cell-free DNA (cfDNA) analysis is an important tool for cancer monitoring. The patient-specific mutations identified in colorectal cancer (CRC) tissues are usually used to design the cfDNA analysis. Despite high specificity in predicting relapse, the sensitivity in most studies is around 40–50%. To improve this weakness, we designed a cfDNA panel according to the CRC genomic landscape and recurrent-specific mutations. The pathological variants in cfDNA samples from 60 CRC patients were studied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…We demonstrate an overall ctDNA persistence of ∼9% in stage II CRC patients after surgery, which confirms recent data on the frequency of postoperative ctDNA persistence (Tie et al, 2016;Reinert et al, 2019). In addition, tumor-informed ctDNA was detected 1-8 months prior to imaging-based detection of progression in 92.85% of CRC patients with relapse, which is in the range or superior to rates (72-92.3%) determined previously (Tie et al, 2015;Schøler et al, 2017;Reinert et al, 2019;Wang et al, 2019;Luo et al, 2020;Yeh et al, 2020). Interestingly, in two patients (Pat.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We demonstrate an overall ctDNA persistence of ∼9% in stage II CRC patients after surgery, which confirms recent data on the frequency of postoperative ctDNA persistence (Tie et al, 2016;Reinert et al, 2019). In addition, tumor-informed ctDNA was detected 1-8 months prior to imaging-based detection of progression in 92.85% of CRC patients with relapse, which is in the range or superior to rates (72-92.3%) determined previously (Tie et al, 2015;Schøler et al, 2017;Reinert et al, 2019;Wang et al, 2019;Luo et al, 2020;Yeh et al, 2020). Interestingly, in two patients (Pat.…”
Section: Discussionsupporting
confidence: 88%
“…In line, sensitivity for low-level ctDNA increased by increasing the input of cfDNA as PCR template and by the integration of sequencing reads from triplicate PCRs, pointing to an “all-or-nothing” positive amplification in samples with low mutant DNA copy numbers and a potential benefit of binning for barcoded sequencing reads. In combination with sufficient sequencing depth (≥100.000 reads), the sensitivity of our error-reduced NGS approach (0.01% VAF) is one to two orders of magnitude higher than conventional targeted NGS procedures (typically 0.1–1% error) ( Rachiglio et al, 2016 ; Osumi et al, 2019 ) and similar to sensitivities determined for digital droplet PCR ( Demuth et al, 2018 ) or for other modified NGS protocols ( Yeh et al, 2020 ). Turnaround time for analysis (24–48 h) and costs (∼45€ per sample) of our NGS-based procedure are slightly higher than ddPCR (8 h, <20€) and are in the range of other PCR-based approaches with similar sensitivities for cfDNA analysis such as BEAMing ( Demuth et al, 2018 ; Garcia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…a study conducted on 158 plasma samples from disease positive and negative groups showed that low level (< 10 ng/ml) of ccfDNA were observed in disease negative group while elevated ccfDNA concentration (1.180 to 321 ng/ml) was detected in CRC patients [ 130 ]. Furthermore, the study also determined an optimal ccfDNA concentration cutoff of 7.0 ng/ml as sensitive and specific concentration to discriminate diseased from control groups [ 130 ]. Though an interesting finding, there are several limitations to this approach.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 20 For example, the cfDNA concentrations in patients with colorectal cancer could serve as the first threshold to categorize ‘disease-positive’ and ‘disease-negative’ recurrent groups. 33 In the present study, we used the average cfDNA value between the initial and after two cycles of chemotherapy as the threshold to determine whether NDM occurred. There were no evident cfDNA levels in patients without NDMs, implying that there was a baseline cfDNA level in the blood.…”
Section: Discussionmentioning
confidence: 99%